ANALISIS REFORMASI BIROKRASI DI BADAN PUSAT STATISTIK SEBAGAI SISTEM TERBUKA - Yuni Anggorowati (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2018)
The purpose of the research is to analyze the bureaucratic reform process at the Badan Pusat Statistik (BPS-Statistics Indonesia). The research used organizational approach as an open system. This approach is carried out to provide an overview of how BPS strategic environment, as a source of information to review the background, processes and achievements of bureaucratic reform. As the basis for formulating policies, especially improving human resources and public services. This study uses descriptive methods to examine each stage of the bureaucratic reform process. the results of this study shows that the BPS bureaucratic reform is a process of adaptation to environmental changes to reach a higher level.